The isolation and identification of antimalarial agents of the n-hexane fraction of the neem leaves (Azadirachta indica A. Juss) - . Suryawati; Hanifah Yusuf; . Sofia (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Abstract. Following the study which confirmed the antimalarial activity of the n-hexane fraction of the neem leaves (Azadirachta indica A.Juss), a research that aimed to reveal the active compounds act as antimalarial agents had been conducted. In this study, the n-hexane fraction of neem leaves were analyzed using the phytochemical, spectroscopic and chromatographic methods.  The chemical compounds, suspected to have an antimalarial activity, were isolated using the thin-layer chromatographic method with several solvents which different in their polarity. The visualizing reagents were used to characterize the compounds. The result showed that the n-hexane fraction of neem leaves contained of steroids, terpenoids and fenols. Analysis by gas chromatography-mass spectroscopy showed that fenol derivatives existed in the largest amount. The compounds were identified as benzyl benzoat (25.63%), tetracosane (17.51%) and hexadecanal (14.61%)